Peran Guru Agama Islam Dalam Memotivasi Belajar Untuk Meningkatkan Akhlak Siswa di SMA Muhammadiyah 23 - Rizal Nur Wahid; Totong Heri (Departement of Mathematics Education, 2024)
This research aims to examine the role of Islamic religious teachers in motivating students to improve the morals of students at SMA Muhammadiyah 23, where the role of Islamic religious teachers is expected to improve students' morals because teachers directly interact with students in the classroom, and motivation is an effort from teachers to encourage students' learning outcomes, so that they can improve students' morals. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. The respondents of this research were Al-Islam Kemuhammadiyahan teachers and students at SMA Muhammadiyah 23. The research results showed that the role of Islamic religious teachers in motivating students had an effective role in improving students' morals because Islamic religious teachers interacted directly with students and motivated students. with the learning method used in the learning process.